Low-Value Inpatient Gastrointestinal Practices among Non-Gastroenterologists - Arora, MD, Sumant; Ahmed, Zunirah; Sidhu, MD, Gurpratap; Young, MD, Steven; Khan, MD, Muhammad Yasir; Agrawal, MD, Deepak; Atiq, MD, Omair (North American Journal of Medicine and Science, 2020)
Background and Aims: Management of common gastrointestinal diseases by non-gastroenterologists often includes diagnostic tests that do not positively impact patient care but increases cost of care. Our study aimed to determine the prevalence of common inpatient practices by non-gastroenterologist providers. Methods: A validated anonymous survey was designed using ‘Google Forms’ (google.com/forms) and responses were collected on a handheld tablet. The questions included basic demographics, level of training, training specialty and practices related to common gastrointestinal diseases. The practices included fecal occult blood testing (FOBT), recognition of melena, use of lipase in management of acute pancreatitis, placement of nasogastric tube in cirrhosis, duration of nil per oral (NPO) before procedures and international normalized ratio (INR) threshold for paracentesis. Descriptive analysis was performed. Results: We collected 150 responses from 4 different residency training hospitals in the United States. Of the respondents, 84% were resident trainees. Primary specialties of practice were internal medicine (82%), family medicine (11%), and others (7%). Inpatient FOBT was available in 95% of the facilities surveyed. With regards to melena, 77.5% correctly identified it as black tarry stool, but 17% also considered FOBT positive brown stool as melena. 21% correlated high lipase levels with more severe acute pancreatitis.19% considered history of cirrhosis a contraindication for placement of nasogastric tube. Only 35% performed abdominal paracentesis regardless of INR value. Discussion: Low value tests and procedures related to common gastrointestinal diseases are prevalent among non-gastroenterologists. Better communication between primary team and specialist and education is needed to optimize patient care.